Analysis of an automated solar panel cleaning robot on photovoltaics (PV) module frames with composites materials - Murshiduzzaman; As'Arry, Azizan; Lim, Wei Keong; Mohamed Yusoff, Mohd Zuhri; Salit, Mohd Sapuan; Supeni, Eris Elianddy; Wan Hasan, Wan Zuha; Yussof, Hanafiah (Walter de Gruyter, 2025)
Solar panels are essential for harvesting clean energy from the sun, but dust collection can dramatically limit their efficiency and power output. This challenge has led to the development of automated solar panel cleaning robots, a promising solution to ensure the continuous and optimal performance of solar arrays. One concern is that the cleaning method can cause long-Term damage or degradation to the panels, such as cracking, if the cleaning robot is not positioned correctly on the solar panel. The risk of damage or degradation to solar panels during the cleaning process is a significant consideration for both manufacturers and operators of solar installations. Automated solar panel cleaning robots are valuable tools in maintaining the efficiency and longevity of solar arrays. However, their deployment requires a balanced approach that prioritizes effective cleaning while minimizing the risk of damage to the panels.